Laboratory determination of old and new targeted anticoagulant agents for prevention of bleeding and thrombotic events in cancer patients - Harenberg, Job (Thrombosis research, 2016)
A two-fold prolongation of activated partial thromboplastin time (APTT) is established as therapeutic range for therapy with unfractionated heparin, hirudin and argatroban. The international normalized ratio (INR) of 2 to 3 is required to maintain anticoagulation in the therapeutic range of vitamin K antagonists. The therapeutic range of anti-factor Xa activity during therapy with low-molecular weight heparins and danaparoid are less well and of direct oral anticoagulants (DOAC) poorly defined. The relation of aPTT and INR values to thrombotic and bleeding events are well established despite a large variation of values in affected patients. The relation of coagulation values of the other anticoagulants to clinical events is open. The value of determination in cancer patients is higher because of the increased risk for thrombotic and bleeding events of this patient group. Several activities are currently undertaken to certify methods for in vitro diagnostic testing for DAOCs.
Gesehen am 26.08.2019